2020
DOI: 10.17826/cumj.661260
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence and quality of life according to trimesters in pregnancy

Abstract: The aim of this study was investigate the effect on life quality (QOL) of urinary ıncontinence (UI) according to trimesters in pregnancy. Materials and Methods: The study was conducted between the study was conducted between the 2017-2018 year and a total of 195 pregnant women with UI, 75 of which were from second trimester and 120 of third trimester were included in the study. Data were collected by Personal Information Form, Urinary Incontinence Questionnaire Short Form (ICIQ-SF) and Incontinence Quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
1
0
1
Order By: Relevance
“…Another positive attitude is that most pregnant women consider UI as a barrier affecting social life. Similarly, in previous studies, it was indicated that UI during pregnancy physically, socially, and psychologically affected negatively of quality of life 10 , 13 , 16 . Therefore, knowing that their quality of life will be affected when UI cannot be prevented or managed may increase their health-seeking behaviors.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Another positive attitude is that most pregnant women consider UI as a barrier affecting social life. Similarly, in previous studies, it was indicated that UI during pregnancy physically, socially, and psychologically affected negatively of quality of life 10 , 13 , 16 . Therefore, knowing that their quality of life will be affected when UI cannot be prevented or managed may increase their health-seeking behaviors.…”
Section: Discussionsupporting
confidence: 64%
“…UI negatively affects women's quality of life physically, psychologically, sexually and socially. In the study of Gokalp et al, it was found that the quality of life of pregnant women with UI was affected the most in the area of limitation of behavior, and the least in the psycho-social area 16 . Inal and Timur found that with the increase in urinary symptoms of pregnant women, the quality of life decreased in the subdimensions of limiting behaviors, psychosocial influence and social isolation 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Çeşitli yaş gruplarında ve durumlarda yapılan araştırmalarda Üİ'nin yaşam kalitesini düşürdüğü belirtilmiştir. [20][21][22][23][24] Yetişkinlerde yaşam kalitesi üzerinde olumsuz etkileri olan üriner inkontinansın aynı şekilde üniversite öğrencilerinin yaşam kalitesinide olumsuz şekilde etkilediği saptanmıştır. 15 Aksu (2014), 15-24 yaş grubundaki kızlarla yapmış olduğu araştırmada, inkontinansın yaşam kalitesini etkilediği tespit edilmiştir.…”
Section: Gereç Ve Yöntemunclassified